Analisis Wacana Digital Cancel Culture terhadap Abidzar dalam Konten YouTube Cokro TV - Bakir, Muhammad Rizqi Raihan; Nurhaqiqi, Hanna (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study examines the phenomenon of cancel culture in the Indonesian film industry through a case study of actor Abidzar Al-Ghifari and the controversy surrounding the film A Business Proposal. The controversy arose from Abidzar’s statement during a press conference, which was perceived as belittling the original Korean drama, triggering negative reactions in digital spaces. This research employs a descriptive qualitative approach using Rodney H. Jones’s Digital Discourse Analysis method, which includes four elements: text, context, action and interaction, and power and ideology. Data were collected from a YouTube video by Cokro TV titled “Gegara Kesombongan Abidzar, Falcon Rugi Bandar! featuring Ade Armando” and its comment section. The findings reveal that cancel culture functions as a form of social expression, with netizens acting as moral gatekeepers in digital spaces. The discourse reflects the power dynamics between public figures and digital society, who collectively construct legitimacy through social media. This phenomenon significantly affects reputation, career, and the continuity of film projects.